The Influence of Health Worker Communication, Patient Engagement, and Service Coordination on the Quality of Service at Harapan Bunda Banda Aceh Hospital Based on Patient-Centered Care - Dewi Yuliana Fithri; Innocentius Bernarto (Politeknik Siber Cerdika Internasional, 2026)
Background: Hospital service quality remains a challenge in Indonesian private hospitals, and evidence on how Patient-Centered Care (PCC) influences service quality remains limited. Objective: This study aimed to analyze the influence of health worker communication, patient engagement, and service coordination on the quality of hospital services based on Patient-Centered Care at Harapan Bunda Banda Aceh Hospital. Methods: This quantitative cross-sectional study involved 287 outpatients and inpatients selected through purposive sampling. Data were collected using a validated Likert-scale questionnaire and analyzed using Pearson’s correlation and binary logistic regression. Results: The results showed that health worker communication had a positive and significant relationship with hospital service quality, with a correlation coefficient of 0.64 and an odds ratio (OR) of 3.74 (p = 0.001). Patient engagement also significantly influenced service quality, with a correlation coefficient of 0.58 and an OR of 2.59 (p = 0.004). Furthermore, service coordination had a positive and significant influence on service quality, with a correlation coefficient of 0.60 and an OR of 2.86 (p = 0.003). Collectively, the three variables accounted for 66% of the variation in hospital service quality (Nagelkerke R² = 0.66). The Hosmer–Lemeshow goodness-of-fit test indicated that the model adequately fit the data (χ² = 5.874, p = 0.672). Health worker communication was identified as the most dominant variable influencing hospital service quality. Conclusion: This study concludes that implementing Patient-Centered Care principles through effective health worker communication, active patient engagement, and well-coordinated services can significantly improve the quality of hospital services.